Tracing the path to retail gentrification: insights from Marvila, Lisbon - Guimarães, Pedro (2022)
Retail gentrification is a rising field of research within the wider field of gentrification studies. In this paper we use the old neighbourhood of Marvila in Lisbon as a case study. The information collected from the fieldwork demonstrates the depth of transformations occurring in the commercial fabric of Marvila, which is having a detrimental effect on old stores and the local population. Moreover, it reveals that the current process was triggered by a group of independent investors, whose success is placing them at risk of being displaced. These findings reinforce the existent body of literature on the subject of retail gentrification.